A Pilot Study Exploring Age Differences in Presence, Workload, and Cybersickness in the Experience of Immersive Virtual Reality Environments - Dilanchian, Andrew T.; Andringa, Ronald; Boot, Walter R. (Frontiers in Virtual Reality, 2021)
Research is often focused on understanding barriers to the use and adoption of technology to support older adults’ (65+) instrumental activities of daily living (IADLs), such as communication, banking, and transportation. Less attention is paid to technology to support enhanced activities of daily living (EADLs), activities that enrich our daily lives, even though they have the potential to improve wellbeing, promote physical and emotional health, and reduce stress. Here, we explored how older adults interacted with commercial virtual reality (VR) to investigate the feasibility of using VR as an EADL support system. Older adults navigated different VR environments, including environments that were meditation, exploration, and game-oriented. Of particular interest was whether older adults (N = 20) psychologically experienced differing degrees of presence within virtual environments compared to younger adults (N = 20), and potential barriers to use as assessed by measures of workload and system usability. Given previously observed age-related differences in cybersickness, this was also assessed as a potential barrier. Compared to younger adults, older adults expressed a greater sense of presence in virtual environments, with nonsignificant differences in perceived workload and usability according to most measures. Contrary to expectations, older adults reported significantly less cybersickness compared to younger adults. Results suggest that VR is a promising means to support older adults’ EADLs.